The influence of leadership and payment for performance on individual performance - Laura Pinheiro Zebral (Journal of Applied Leadership and Management, 2017)
Research Questions: Are the effects of productive leadership on individual working performance higher than the effects of pay-for-performance programs? Methods: Empirical study using survey to evaluate the correlation between individual working perfor-mance of employees, pay-for- performance schemes and productive leadership. Results: Productive leadership influences individual performance of employees more than pay-for-per-formance schemes.
Keywords: 650; leadership; pay-for-performance programs